Outcomes of internal fixation with Femoral Neck System (FNS) for intracapsular femoral neck fractures - Seth A. Tarrant, MD; Brendan P. Mitchell, MD; Michael G. Blankespoor, MD; Zane D. Littell, MD; Rosalee E. Zackula, MA; Randall L. Lais, MD; Bradley R. Dart, MD (OTA International, 2024)
Abstract. Background:. Internal fixation of hip fractures is associated with high reoperation rates. This study investigated the reoperation rates after internal fixation with the femoral neck system (FNS). Materials and Methods:. A single-institution cohort study was conducted on patients aged 18 years or older who sustained intracapsular femoral neck fractures and underwent internal fixation with a fixed-angle implant. Surgeons, patients, and investigators were not blinded. The primary outcome was any hip reoperation at the final follow-up. Secondary outcomes were to characterize a cohort of patients regarding demographics, fracture classification, intraoperative findings, postoperative fracture complications and union rates, and postoperative pain. Results:. This study found that internal fixation with FNS for intracapsular femoral neck fractures was associated with a 23% rate of revision surgery. Of the initial 94 patients who received FNS internal fixation, 44 patients were included for analysis; of those, 10 patients underwent revision surgery. Patients had a 22% rate of in-hospital medical adverse events with a 30-day readmission rate of 9%. Increasing body mass index was associated with increased revision rates (P = 0.037). Patients who sustained displaced femoral neck fractures had a significant decrease in SF-12 Mental Health Composite, SF-12 Physical Health Composite, and quality-of-life subscale scores. Conclusions:. The FNS is a viable alternative for internal fixation of intracapsular femoral neck fractures. The observed rate of revision after internal fixation was comparable with previously published outcomes following fixation with cannulated screws and sliding hip screws. Level of Evidence:. Level IV, Therapeutic Study.